2000
DOI: 10.1128/jvi.74.19.9184-9196.2000
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis and Nuclear Trafficking of Adeno-Associated Virus Type 2 Are Controlled by Rac1 and Phosphatidylinositol-3 Kinase Activation

Abstract: Adeno-associated virus (AAV) is a single-stranded DNA parvovirus that causes no currently known pathology in humans. Despite the fact that this virus is of increasing interest to molecular medicine as a vector for gene delivery, relatively little is known about the cellular mechanisms controlling infection. In this study, we have examined endocytic and intracellular trafficking of AAV-2 using fluorescent (Cy3)-conjugated viral particles and molecular techniques. Our results demonstrate that internalization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
217
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(231 citation statements)
references
References 66 publications
(65 reference statements)
12
217
2
Order By: Relevance
“…39 To this end, soluble heparin can compete for binding of AAV2 to the surface of many cell types. 39,40 Mutagenesis and crystal structure studies have identified the amino acids in the capsid of AAV2 responsible for HSPG binding. 41,42 Heparin has also been reported to compete for AAV3 binding to cells, implying that AAV2 and AAV3 may share HSPG as an attachment receptor.…”
Section: Aav Attachment Receptors and Coreceptorsmentioning
confidence: 99%
See 4 more Smart Citations
“…39 To this end, soluble heparin can compete for binding of AAV2 to the surface of many cell types. 39,40 Mutagenesis and crystal structure studies have identified the amino acids in the capsid of AAV2 responsible for HSPG binding. 41,42 Heparin has also been reported to compete for AAV3 binding to cells, implying that AAV2 and AAV3 may share HSPG as an attachment receptor.…”
Section: Aav Attachment Receptors and Coreceptorsmentioning
confidence: 99%
“…52,53 Nonetheless, inhibition of aVb5 integrin with blocking antibodies can prevent internalization of bound rAAV2 on the surface of HeLa cells. 40 Similarly, platelet-derived growth factor receptor (PDGFR) has been considered the coreceptor for AAV5 and is also required for efficient infection with this serotype. 54 However, PDGFR itself is a sialo-glycoprotein containing both N-and O-linked oligosaccharide chains with sialic acid.…”
Section: Aav Attachment Receptors and Coreceptorsmentioning
confidence: 99%
See 3 more Smart Citations